Empowerment Model of Micro, Small, and Medium Enterprises (MSMES) Village Tourism Business in e-Commerce Transactions and Legal Protection - PURWANINGSIH, Endang; SUHAERI, SUHAERI (Journal of Advanced Research in Law and Economics, 2019)
Producers of Micro, Small and Medium Enterprises (MSMEs) in the Business Tourism Village, Tegal Waru, Bogor no one has a registered trademark, only label usage on perfunctory packaging, but there are low quality products that are similar to well-known trademark. Manufacturers also conduct conventional transactions. Producers have also not been touched by the regional government and related agencies optimally. The main objectives of this study are: examine the appropriate empowerment model for producers of MSMEs in e commerce transactions and examine the forms of legal protection needed to empower MSMEs producers in Tegal Waru, Bogor. This study uses a literary study and is supported by in depth interviews, with a statute approach, sociologish approach and historish approach, so that data is obtained from both the literature and interviews and support from the results of the questionnaire. The fix empowerment model for MSMEs in Tegal Waru, Bogor in e commerce transactions is to revitalize the role of the organization, the role of the village officials and producers as well as the organization and government's alignments with MSMEs producers in Tegal Waru, especially the Bogor Regency Cooperative Office. The form of legal protection needed to empower producers of MSMEs in Tegal Waru Bogor in e-commerce transactions is legal protection in buying and selling, protection of intellectual property in this case the trademark, and legality of business entities and legal certainty of online transactions.